Exonization of active mouse L1s: a driver of transcriptome evolution? - Badge Richard; Dandekar Thomas; Schultz Jörg; Penzkofer Tobias; Zemojtel Tomasz; Vingron Martin (BMC Genomics, 2007)
Abstract Background Long interspersed nuclear elements (LINE-1s, L1s) have been recently implicated in the regulation of mammalian transcriptomes. Results Here, we show that members of the three active mouse L1 subfamilies (A, GF and TF) contain, in addition to those on their sense strands, conserved functional splice sites on their antisense strands, which trigger multiple exonization events. The latter is particularly intriguing in the light of the strong antisense orientation bias of intronic L1s, implying that the toleration of antisense insertions results in an increased potential for exonization. Conclusion In a genome-wide analysis, we have uncovered evidence suggesting that the mobility of the large number of retrotransposition-competent mouse L1s (~2400 potentially active L1s in NCBIm35) has significant potential to shape the mouse transcriptome by continuously generating insertions into transcriptional units.